Evidence for re-infection and persistent carriage of Shigella species in adult males reporting domestically acquired infection in England. (January 2021) - Allen, H.; Mitchell, H.D.; Simms, I.; Baker, K.S.; Foster, K.; Hughes, G.; Dallman, T.J.; Jenkins, C.
Abstract: Objectives: We analysed national surveillance typing data of Shigella isolated from adult males with domestically acquired infection (a cohort largely consisting of men who have sex with men (MSM)) to establish whether multiple isolates from the same individual over time represented persistent carriage or re-infection. Methods: We carried out a retrospective cohort study of adult males diagnosed with Shigella from 2004 to 2018. Median time intervals between multiple isolations of Shigella flexneri and S. sonnei were compared. Analysis of whole genome sequencing data provided strain discrimination at the single nucleotide level and was used to quantify the genetic distance among isolates. Maximum likelihood phylogenies were constructed to determine whether persistent carriage (characterized by multiple isolations of the same strain) or re-infection (characterized by multiple isolations of different strains) was best supported by the phylogenetic analysis. A comparison analysis was carried out using data linked to adult females with domestically acquired shigellosis. Results: The number of men reporting multiple isolations of Shigella species was 165/4733 (3.5%) compared with 31/2423 (1.3%) females (p < 0.001). For isolate pairs from men associated with persistent carriage, the isolation time interval range was 6–176 days (median 23.5; IQR 8–70) and single nucleotide polymorphism (SNP) distance range was 0–7 SNPs (median 0.5; IQR 0–2). For those associated with re-infection, the isolation time interval was 34–2636 days (median 732; IQR 191–1258) and the SNP distance was 10–1462 SNPs (median 120; IQR 29–377). Discussion: Multiple Shigella isolations in individuals with domestically acquired infections was more frequently observed in adult males than in adult females. Following the acute phase of infection, carriage can persist for months, and infection can recur within months, even with strains belonging to the same species and the same serotype. A combination of multiple sexual partners, persistent carriage following the acute phase of infection and evidence of recurrent re-infection is likely to contribute to sustained transmission in this population.